Brain and behaviour in primate evolution - Dunbar, R (Springer-Verlag Berlin Heidelberg, 2010)
Primates have unusually large brains for body size compared to all other vertebrates. Over the years, a number of explanations have been offered for this, leading to some confusion. I use a systems approach to make sense of these suggestions, and this suggests that some are constraints (energetic or neural development explanations), others consequences (generated by windows of opportunity), but only the social hypotheses constitute the real selective pressure for the evolution of brains. The social hypotheses come in two current forms (bonding social groups vs. social learning of foraging skills) that differ in whether predation or food-finding are assumed to be the rate-limiting factor in primate survival. While the standard form of the social brain hypothesis in primates is a quantitative relationship between social group size and brain size, comparative analyses for other mammal and bird taxa reveal that it takes a purely qualitative (i.e., categorical) form in all nonprimates examined so far: species with pairbonded (i.e., monogamous) mating systems have larger brains than all others. I suggest that this difference is due to the fact that anthropoid primates developed bonded social systems early in their evolutionary history. Finally, I consider briefly the implications of these findings for human evolutionary history.